Análise genética e antigênica do ectodomínio da glicoproteína E2 de pestivírus isolados de bovinos no Rio Grande do Sul, Brasil - Freitas, Carolina de Oliveira (2020)
The bovine pestiviruses, bovine viral diarrhea virus 1, 2 (BVDV-1, BVDV-2) and HoBi-like (HobiPeV) are associated with several reproductive and clinical manifestations, producing important losses for the cattle industry. Field isolates have a significant genetic and antigenic variability, especially in the envelope glycoprotein E2. This variability may compromise molecular and immunological diagnosis and immunization strategies. Thus, this study performed a genetic and antigenic analysis of 51 pestivirus isolates obtained from beef cattle in Rio Grande do Sul, Brazil, in 2017. Initially, the isolates were identified by PCR and confirmed by sequencing and phylogenetic analysis of the 5'UTR region of the genome, complementing an analysis previously carried out in a more comprehensive region of the 5'UTR. Then, the isolates were submitted to reactivity assays with 11 monoclonal antibodies (MAbs) to the E2 glycoprotein, followed by sequencing and analysis of the domain A (DA) of the E2 ectodomain. Based on the phylogenetic analysis of the 5’UTR, 27 isolates were identified as BVDV-1 (22 -1a and 5 of -1b), 23 as BVDV-2 (all as -2b) and one as HobiPeV(-3a). This subtyping corresponded to a previous study that characterized the entire portion of 5'UTR. Sequence analysis (nucleotide and amino acid) of the E2 DA domain identified several nucleotide and amino acid changes, mainly at immunodominant sites subjected to binding by antibodies. The amino acid residues that presented the highest variability were at sites: 695 and 782 on the bovine pestivirus genome. Fewer aa changes were also observed at position 701 and 734. MAb binding assays revealed marked variability in most E2 epitopes. On the other hand, some MAbs recognized almost all isolates, confirming the existence of highly conserved epitopes in E2, while other MAbs recognized few or no isolates. Thus, the present study provides important information about the genetic and antigenic variability of the E2 DA domain of bovine pestivirus. This information may be useful to guide molecular an immunological diagnosis and for vaccine formulation as well.